Two-Year Monitoring of Staphylococcus aureus Contamination in Traditional Shahroud Kebab and Ice Cream and Its Consequences on Public Health - Masoudi, Alireza; Javaheri, Tayebeh; Kordi, Zahra; Ebrahimi, Mohammad Hossein; Miri, Seyed-Mahya; Tabatabaei, Seyed-Zohreh; Dabagh Mazhari, Mohammad-Reza; Ghanbarian, Marjan (Shahroud Journal of Medical Sciences, 2025)
Background: Staphylococcus aureus is a common enterotoxin-producing bacteria that can grow in food products such as kebabs and ice cream and cause food poisoning.Methods: Using standard food sampling methods, over the course of two years from 2022 to 2024, samples of kebab and ice cream were collected from all traditional ice cream and traditional kebab stores in Shahrood, with a total number of 252 samples, and the amount of Staphylococcus aureus in these samples was examined according to the standard method of the Food Control Department.Results: In terms of examining the contamination of the samples examined with Staphylococcus aureus bacteria, 37 cases (14.7%) were identified as positive out of a total of 252 samples. To examine the seasonal relationship and sample type, the chi-square test and logistic regression were used. The results showed that there was no significant relationship between the type of sample and the result of contamination with Staphylococcus aureus (P-value>0.05). The results of the logistic regression analysis also showed that the type of sample had no effect on the result of contamination.Conclusions: The results of the present study show that the health index of kubideh kebab and chicken kebab, as well as ice cream in Shahroud city, is at a suitable level compared to other studies, which is attributed to the observance of hygiene in this area.